Enzyme studies in the tricarboxylic acid cycle - Morrison, J (1953)
The purpose of this investigation was to obtain a highly purified preparation of aconitase and to study the properties of the purified enzyme. The thesis describes The method of purification The activation of aconitase by Fe24 and reducing agents The effect of pH on the enzyme activity The study of the Kinetics of the enzyme The effect of fluorocitric acid on the enzyme activity The effect of other inhibititors on the enzyme activity. The results may be briefly summarised as follows: A preparation of aconitase with a higher specific activity than previously reported has been obtained. The preparation was stable. Electrophoretic analysis showed that the aconitase protein formed 75-80% of the total protein present. The results obtained during the fractionation were consistent, with the idea that aconitase activity is associated with a single species of protein molecule. The final enzyme preparation possessed little activity in the absence of Fe2+ and a reducing agent. The activity could be increased 70-fold by the presence of these substances. The results indicate that the active form of the enzyme is an enzyme-Fe2+-activator complex. from a study of the effects of pH on the reactions catalysed by aconitase and of the reaction Kinetics, it was concluded that the same catalytic centre of the aconitase protein is concerned in all the reactions Aconitase was inhibited in a competitive fashion by 'natural' fluorocitric acid, whilst synthetic fluorocitric acid inhibited it competitively and irreversibly. Whereas pchloromercuribenzoate inhibited aconitase in the presence of substrate, o-phenanthroline, 2:2'- dipyridyl and versene inhibited only in the absence of substrate. Cyanide and azide did not inhibit the enzyme.